Penggunaan Alat Bukti Petunjuk Dalam Pembuktian Tindak Pidana Persetubuhan - Wiguna, Thomas Adi; Santoso, S.H., M.Hum, Bambang (Sebelas Maret University, 2017)
This study aimed to know the used of evidences in process of authentication indictment of criminal act deliberately persuading the child to intercourse with him as the basis judgement by the judge in decide the case in case study on the verdict number 78/pid.b/2013/pn.unh. On Saturday, April 6, 2013 at 10:00 pm at the health center located Ladianta district. Wawonii Northeast District. Konawe. Defendant Suzan Azim Als. Yaumi have intercourse with the victim and threatened to kill the victim and the victim's family, the victim just shut up and then cry, victim and the defendant out of the room and defendant told the victim to return to school. In this criminal act, general prosecutor indicted the defendant with alternative subsidiary indictment. The process of proving in court showed that the evidence used in proving the crime of intercourse is in conformity with the provisions of Article 184 of the Criminal Procedure Code of evidence. Evaluation of the results of proof in Decision Number 78/Pid.B/2013/PN.Unh has given confidence to the judge that the defendant has committed the crime and sentencing of the accused in accordance with Article 183 of the minimum evidence in conjunction with Article 193 paragraph (1) criminal Code that if the court found the defendant guilty of the crime against her, the court dropped criminal. Keywords: evidence, authentication, criminal acts of intercourse